Kültürel diplomasi bağlamında Ayasofya'nın Türkiye- Avrupa Birliği ilişkilerindeki rolü - Oktay, Begüm (My University, 2023)
Ayasofya, asırlardır hem dini hem de politik önemini korumuş dini bir mabet statüsündedir. 1453’te Fatih Sultan Mehmet’in İstanbul’u fethiyle Osmanlı Devleti’nin hakimiyetine giren Ayasofya, kilise olarak başladığı tarihi yolculuğuna cami olarak devam ederek yüzyıllarca önemli bir islam mabedi haline gelmiştir. Ayasofya, asırlardır hem dini hem de politik önemini korumuş dini bir mabet statüsündedir. 1453’te Fatih Sultan Mehmet’in İstanbul’u fethiyle Osmanlı Devleti’nin hakimiyetine giren Ayasofya, kilise olarak başladığı tarihi yolculuğuna cami olarak devam ederek yüzyıllarca önemli bir islam mabedi haline gelmiştir. Bu çalışmada, kültürel diplomasi bağlamında, asırlardır önemini koruyan Ayasofya’nın bir yumuşak güç olarak kullanılmasının, Türkiye- Avrupa Birliği ilişkilerine nasıl bir etkisi olduğu dış basına yansımaları ile araştırılmıştır.

The Hagia Sophia features the status of a religious edifice which has maintained both its religious as well as political significance for centuries. The Hagia Sophia, which came under domination of the Ottoma Empire upon conquest of Istanbul by Sultan Mehmed the Conqueror in 1453, continued its journey in history, which it began as a church, as mosque and has become a major edifice of islam throughout the centuries. The building, which was used as mosque during the era of the Ottoman Empire, was serving as a museum since 1935 upon in the establishment of the Republic of Turkey. Due to the significance of the Hagia Sophia for the Christians and following its conversion into a mosque, and since it has become a symbol of the conquest of Istanbul for the muslim people, the Hagia Sophia discussions have continued over the years. The argumentation as to “Is the Hagia Sophia a mosque or a church?” may be considered as one of the political issues between Greece and Turkey, and the problems between Greece and Türkiye affect Türkiye’s relationships withthe European Union. In this study, the effect of the change of status of Hagia Sophia, which has been maintaining its importance for centuries, and the effect of its being used as a soft power, on the Türkiye – European Union relations within the context of cultural diplomacy, has been analysed from the point of view of its reflections in external media.
Hagia Sophia's role in the European Union - Türki̇ye relations in the sense of cultural diplomacy
Keywords: Algı; Alman Medyası; Avrupa Birliği; Ayasofya; Ayasofya (İstanbul, Türkiye); Cultural Diplomacy; European Union; German Media; Greek Media; Hagia Sofia (Istanbul, Turkey); Hagia Sophia; Intercultural communication; Kamuoyu; Kültürel Diplomasi; Kültürlerarası iletişim; Management; Perception; Propaganda; Public Opinion; Soft Power; Yönetimi; Yumuşak Güç; Yunan Medyası